Tingkat Kesukaan Tikus Terhadap Berbagai Umpan Pada Perangkap Semi Otomatis - Mahmudah Mamudah; M Indar Pramudi; Yusriadi Marsuni (JURNAL PROTEKSI TANAMAN TROPIKA, 2022)
Field rats can be controlled by biological control, technical culture, physical mechanics or chemistry, while the most effective and efficient way is to use traps, in addition to reducing environmental pollution. This method is also safe and economical and can be used repeatedly. This control also uses bait to attract rats, bait used by rice field crabs, salted tuna, roasted coconut, roasted coconut and shrimp paste. This study aims to determine the bait that can attract the attention of field rats in semi-automatic traps and the benefits of being able to provide information for farmers to overcome rice field rat pests by using bait to attract rats into the trap. The research method used was a one-factor Completely Randomized Design (CRD) experiment with 5 treatments. The results showed that the treatment of each bait seen statistically had no significant effect, but the baits that were preferred by rice field rats were roasted coconut and roasted coconut. This bait can trap three species of rats, namely Rattus exulans, Rattus rattus diardii and Rattus argentiventer.